2018
DOI: 10.1002/chir.22849
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of lysine‐4 methylated histone H3 proteins using synchrotron radiation circular dichroism spectroscopy

Abstract: We report structural alterations of histone H3 proteins induced by lysine-4 (K4) monomethylation, dimethylation, and trimethylation identified by using synchrotron radiation circular dichroism spectroscopy. Compared with unmethylated H3, monomethylation and dimethylation induced increases in α-helix structures and decreases in β-strand structures. In contrast, trimethylation decreased α-helix content but increased β-strand content. The structural differences among K4-unmethylated/methylated H3 may allow epigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…For example, it is assumed that H3K36me3 is linked to DNA repair in transcriptionally active regions, and it is thought the DNA repair processes involve drastic structural alterations of chromatin, namely complex of DNA and histone proteins, induced by the post-translational modifications of histones [ 21 , 22 , 26 , 27 ]. However, experimental and theoretical studies on the structural changes of histone, induced by modifications or DNA damage repair processes, are not so abundant [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To precisely understand the mechanism of chromatin structural remodeling, cyclopedic studies of modification-induced structural changes of histones would be necessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is assumed that H3K36me3 is linked to DNA repair in transcriptionally active regions, and it is thought the DNA repair processes involve drastic structural alterations of chromatin, namely complex of DNA and histone proteins, induced by the post-translational modifications of histones [ 21 , 22 , 26 , 27 ]. However, experimental and theoretical studies on the structural changes of histone, induced by modifications or DNA damage repair processes, are not so abundant [ 17 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To precisely understand the mechanism of chromatin structural remodeling, cyclopedic studies of modification-induced structural changes of histones would be necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The contents of the β-strand and turn structures were the same within the error range. For the trimethylations of lysine-4 or lysine-9 residues of H3 (H3K4me3 and H3K9me3, respectively), a decrement in the content of helix structures and an increment of β-strand structures were observed [ 36 , 37 ], showing that the structural alterations observed in H3K4me3 and H3K9me3 were quite different from those of H3K36me3. These results suggest that the structural changes induced by post-translational trimethylations are not uniform, but are rich in variation depending on the sites of methylation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the author assumes that post-translational modifications of histones arise during DDRs [3], because such modifications would alter steric barriers and/or electrostatic interactions between modified amino-acid residues and other residues, possibly changing the stability of structures. Indeed, trimethylation of lysine-4 or -9 of histone H3, which is a post-translational modification induced during DDRs, induces global structural changes [33,34]. The different structural alterations observed for H2A-H2B and H3-H4 might, therefore, be due to different post-translational modifications.…”
Section: Structure (%)mentioning
confidence: 99%
“…On the other hand, chromatin remodeling processes, which are thought to be induced by post-translational modifications of the histones, have not yet been completely elucidated. Although some groups have reported that acetylation [29][30][31][32] and methylation [33][34][35] of histone peptides and proteins induce structural changes in vitro, reports of structural alterations of chromatin or histones during DDR or relationships between such structural alterations and post-translational modifications in vivo are scarce.Recently, our group discovered that the secondary structure alterations of histones are induced by X-ray irradiation of human cancer cells [36][37][38] through circular dichroism (CD) spectroscopic analysis. In the present review, these results and experimental procedures are discussed with the aim of facilitating further studies of chromatin remodeling and DNA damage repair pathways using CD spectroscopy.…”
mentioning
confidence: 99%
See 1 more Smart Citation